(untitled) (Indian Journal of Arid Horticulture, 2025)
Wood apple is an underutilized indigenous fruit tree belonging to the Rutaceae family. It is a slow-growing tree, and owing to this slow growth in the nursery, seedlings take longer to reach the graftable stage. An attempt was made to investigate the effect of GA3 on seed germination and seedling vigour at the nursery of Central Horticultural Experimental Station, ICAR-CIAH, Yejalpur, during June-November 2016-17. Seeds were treated with various concentrations of GA3 (0, 25, 50, 75, 100, 125, 150, 175, 200, 225, 250, and 275 mg/L), and soaked for 48 hours under laboratory conditions. The experiment was laid out in a Complete Randomized Design (CRD), replicated three times. A total of 50 seeds were treated with GA3 for each concentration. The results showed that different levels of GA3 enhanced seed germination and the growth of seedlings as compared to the control. Among the different concentrations of GA3, 150 mg/L exhibited the best response in terms of seed germination (91.98%), seedling shoot length (23.94 cm), root length (24.53 cm), seedling diameter (5.21 mm), number of leaves/seedling (21.23), primary branches/seedling (4.52), and vigour index (4458.27). Higher concentrations of GA3 above 150 mg/L did not improve seed germination and negatively affected the growth parameters. Based on the findings, it can be concluded that 150 mg/L GA3 is the most effective concentration for enhancing seed germination and vegetative growth of wood apple seedlings in nursery.